Who supports Jihadi foreign fighters in Syria and Iraq? Assessing the role of religion- and grievance-based explanations - Eylem Kanol (Behavioral Sciences of Terrorism and Political Aggression, 2024)
This article explores public support for Jihadi foreign fighters, an area largely unexplored in existing literature, despite its relevance to counterterrorism. The study draws on two key theoretical perspectives: grievance-based explanations that propose support for militancy arises from perceived societal injustices, and religion-based explanations that look at the role of religious factors in fostering support for religious militancy. Using original survey data from 5145 Muslim respondents across seven countries (Cyprus, Germany, Israel, Kenya, Lebanon, Palestine, Turkey), the study empirically tests these perspectives. The findings underscore religious fundamentalism as a potent influencer of support for foreign fighters. By providing large-scale survey data and a comprehensive comparative analysis of dominant theories, this research enhances our understanding of the dynamics that underpin public support for Jihadi foreign fighters.
https://doi.org/10.7802/2687
Keywords: 320; Foreign fighters; Jihad; public support; religiosity; fundamentalism; discrimination